Designing Mimics of Membrane Active Proteins - Sgolastra, Federica (2013)
[Image: see text] As a semi-permeable barrier that controls the flux of biomolecules in and out the cell, the plasma membrane is critical in cell function and survival. Many proteins interact with the plasma membrane and modulate its physiology. Within this large landscape of membrane-active molecules, researchers have focused significant attention on two specific classes of peptides, antimicrobial peptides (AMPs) and cell penetrating peptides (CPPs) because of their unique properties. In this account, we describe our efforts over the last decade to build and understand synthetic mimics of antimicrobial peptides (SMAMPs). These endeavors represent one specific example of a much larger effort to understand how synthetic molecules interact with and manipulate the plasma membrane. Using both defined molecular weight oligomers and easier to produce, but heterogeneous, polymers, it has been possible to generate scaffolds with biological potency superior to the natural analogs. In one case, a compound has progressed through a phase II clinical trial for pan)staph infections. Modern biophysical assays highlighted the interplay between the synthetic scaffold and lipid composition leading to negative Gaussian curvature, a requirement for both pore formation and endosomal escape. The complexity of this interplay between lipids, bilayer components, and the scaffolds remains to be better resolved, but significant new insight has been provided. It is worthwhile to consider the various aspects of permeation and how these are related to ‘pore formation.’ More recently, our efforts have expanded toward protein transduction domains, or cell penetrating peptide, mimics. The combination of unique molecular scaffolds and guanidinium) rich side chains has produced an array of polymers with robust transduction (and delivery) activity. Being a new area, the fundamental interactions between these new scaffolds and the plasma membrane are just beginning to be understood. Negative Gaussian curvature is important but the detailed relationships between molecular structure, self)assembly with lipids, and translocation require more investigation. It has become clear that the combination of molecular design, biophysical models, and biological evaluation provide a robust approach to the generation and study of novel proteinomimetics.